Markets for Corporate Debt Securities - Smith, T. (IMF Working Papers; Working Paper ;, 1995)
This paper surveys markets for corporate debt securities in the major industrial countries and the international markets. The discussion includes a comparison of the sizes of the markets for various products, as well as the key operational, institutional, and legal features of primary and secondary markets. Although there are some signs that debt markets may be emphasized in the future by some countries, it remains true that North American debt markets are the most active and liquid in the world. The international debt markets are, however, growing in importance. The paper also investigates some of the reasons for the underdevelopment of domestic bond markets and the consequences of firms shifting their debt financing needs from banks to securities markets.